Bacterial phospholipases C as vaccine candidate antigens against cystic fibrosis respiratory pathogens: The Mycobacterium abscessus model. Issue 18 (27th April 2015) - Le Moigne, Vincent; Rottman, Martin; Goulard, Céline; Barteau, Benoît; Poncin, Isabelle; Soismier, Nathalie; Canaan, Stéphane; Pitard, Bruno; Gaillard, Jean-Louis; Herrmann, Jean-Louis
Abstract Background Vaccine strategies represent one of the fighting answers against multiresistant bacteria in a number of clinical settings like cystic fibrosis (CF). Mycobacterium abscessus, an emerging CF pathogen, raises difficult therapeutic problems due to its intrinsic antibiotic multiresistance. Methods By reverse vaccinology, we identified M. abscessus phospholipase C (MA-PLC) as a potential vaccine target. We deciphered here the protective response generated by vaccination with plasmid DNA encoding the MA-PLC formulated with a tetra functional block copolymer 704, in CF (ΔF508) mice. Protection was tested against aerosolized smooth and rough (hypervirulent) variants of M. abscessus. Results MA-PLC DNA vaccination (days 0, 21, 42) elicited a strong antibody response. A significant protective effect was obtained against aerosolized M. abscessus (S variant) in ΔF508 mice, but not in wild-type FVB littermates; similar results were observed when: (i) challenging mice with the "hypervirulent" R variant, and; (ii) immunizing mice with purified MA-PLC protein. High IgG titers against MA-PLC protein were measured in CF patients with M. abscessus infection; interestingly, significant titers were also detected in CF patients positive for Pseudomonas aeruginosa versus P. aeruginosa-negative controls. Conclusions MA-PLC DNA- and PLC protein-vaccinated mice cleared more rapidly M. abscessus than β-galactosidase DNA- or PBS- vaccinated mice in the context of CF. PLCs could constitute interesting vaccine targets against common PLC-producing CF pathogens like P. aeruginosa.